(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Quality methodologies that increase efficiency and productivity by reducing waste in time, overproduction, overstock, over process among others, are well known in the manufacturing sector, however, these methods that improve quality and reduce waste can be ideally used in all industries where processes where any type of process is carried out. Given this, in this research, an application of lean manufacturing methodology is presented, applied in a government medical warehouse, to optimize their processes and reduce the above-mentioned waste. Once the foundations of this project have been established the Lean Logistics methodology and the appropriate tools are presented and implemented in the government warehouse, then, the improvement is measured to demonstrate the functionality of the implementation of Lean Logistics in the mentioned warehouse.